3-Methyl-4-nitro-5-isatylidenyl-isoxazoles as 1, 3-dipolarophiles for synthesis of polycyclic 3, 3′-pyrrolidinyl-dispirooxindoles and their biological evaluation for anticancer activities. Issue 34 (24th August 2017) - Lin, Bing; Zhang, Wen-Hui; Wang, Dan-Dan; Gong, Yi; Wei, Qi-Di; Liu, Xiong-Li; Feng, Ting-Ting; Zhou, Ying; Yuan, Wei-Cheng
Abstract: Developed herein is a diversity-oriented one-pot multicomponent synthesis of polycyclic 3, 3′- pyrrolidinyl-dispirooxindoles3 via a multicomponent 1, 3-dipolar cycloaddition event of 3-methyl-4-nitro-5-isatylidenyl-isoxazoles2 with azomethine ylides (thermally generated in situ from isatins and proline or thioproline). Products bearing four consecutive stereocenters consist of two oxindole moieties and a polycyclic pyrrolidinyl core, including vicinal spiroquaternary stereocenters fused in one ring structure were smoothly obtained in high yields (up to 85% yield) with good diastereoselectivity (up to >20:1). Valuable features of this method were application of 3-methyl-4-nitro-5-isatylidenyl-isoxazoles as 1, 3-dipolarophiles and the design of new hybrid architectures for biological screenings through the adequate fusion of these sub-units of isoxazole and 3, 3′-pyrrolidinyl-dispirooxindole, generating drug-like molecules. Graphical abstract: Highlights: 3, 3′-Pyrrolidinyl-dispirooxindoles were synthesized. 3-Methyl-4-nitro-5-isatylidenyl-isoxazoles were firstly used as 1, 3-dipolarophiles. Their in vitro anticancer activities have been demonstrated.